Contrast Medium Induced Nephropathy after Endovascular Stent Graft Placement: An Examination of Its Prevalence and Risk Factors. (16th March 2016) - Kawatani, Yohei; Nakamura, Yoshitsugu; Mochida, Yoshihiko; Yamauchi, Naoya; Hayashi, Yujiro; Taneichi, Tetsuyoshi; Ito, Yujiro; Kurobe, Hirotsugu; Suda, Yuji; Hori, Takaki
Abstract : Endovascular stent graft placement has become a major treatment for thoracic and abdominal aneurysms. While endovascular therapy is less invasive than open surgery, it involves the use of a contrast medium. Contrast media can cause renal impairment, a condition termed as contrast-induced nephropathy (CIN). This study sought to evaluate the incidence and risk factors of CIN following endovascular stent graft placement for aortic aneurysm repair. The study included 167 consecutive patients who underwent endovascular stent graft placement in our hospital from October 2013 to June 2014. CIN was diagnosed using the European Society of Urogenital Radiology criteria. Patients with and without CIN were compared. Chi-squared tests, t -tests, and multivariate logistic regression analyses were performed. Thirteen patients (7.8%) developed CIN. Left ventricular dysfunction and intraoperative blood transfusion were significantly more frequent in the CIN group (P = 0.017 andP = 0.032, resp.). Multivariate analysis showed that left ventricular dysfunction had the strongest influence on CIN development (odds ratio 9.34, P = 0.018, and 95% CI = 1.46–59.7). Patients with CIN also experienced longer ICU and hospital stays. Measures to improve renal perfusion flow should be considered for patients with left ventricular dysfunction who are undergoing endovascular stent graft placement.